2008
DOI: 10.2115/fiber.64.159
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an Emulsion Prepared from Silk Sericin and Vitamin E

Abstract: : An emulsion (SR-EM) was prepared from vitamin E and aqueous sericin solution obtained from cocoons of Bombyx mori. Properties such as emulsifying degree, heat stability and radical scavenging activity of SR-EM were compared with those of CS-EM and AL-EM, vitamin E emulsions prepared from casein and bovine serum albumin, respectively. The degree of emulsifying for SR-EM was three times higher than that for CS-EM. CS-EM and AL-EM were a heat-stable emulsion, whereas SR-EM was a heat-labile emulsion because abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The color of sericin powder also depends on heat exposure during degumming process. Kurioka et al23 have also reported that increase in the temperature of HTHP degumming process from 115 to 125°C, the color of sericin changed from dull yellow to dark brown. Tsukada24 have found that the color of sericin cocoon (Nds/Nd‐S) is changed from white to light yellow, deep yellow, light brown, and black on heating from 170 to 210°C.…”
Section: Resultsmentioning
confidence: 94%
“…The color of sericin powder also depends on heat exposure during degumming process. Kurioka et al23 have also reported that increase in the temperature of HTHP degumming process from 115 to 125°C, the color of sericin changed from dull yellow to dark brown. Tsukada24 have found that the color of sericin cocoon (Nds/Nd‐S) is changed from white to light yellow, deep yellow, light brown, and black on heating from 170 to 210°C.…”
Section: Resultsmentioning
confidence: 94%